A study of the metabolism of low and high backfat Southdown sheep at two levels of energy allowance : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Animal Science at Massey University - Morgan, Peter Francis (Massey University, 1989)
The New Zealand meat industry requires that producers supply lean animals for slaughter and, accordingly, payments are structured such that excessive carcase fat is heavily penalized. This requirement is a consequence of the increasing consumer preference for lean meat of high quality, a trend which reflects medical evidence that high fat diets are unhealthy, particularly given modern sedentary lifestyles. Moreover, the modern consumer prefers products which require minimal preparation and contain little waste. Selection for lean growth has therefore become an increasingly important component of sheep selection programmes. The rate of genetic gain in these programmes is to a large degree dependent upon the ability of breeders to identify animals of high genetic merit.
Content removed due to copyright restriction: S. N. McCutcheon, D., Bremmers, R. M., Morgan, P. F., McCutcheon, S. N., & Purchas, R. W. (1988). Effect of plane of nutrition on energy and nitrogen retention and on plasma urea concentrations in Southdown ram hoggets from high and low backfat selection lines. New Zealand Journal Of Agricultural Research,31 (1), 1-7
Keywords: Southdown sheep; Sheep meat production